Cross-national investigation and prosecution of intellectual property crimes: the example of "Operation Buccaneer" - Urbas, Gregor (Crime, law and social change, 2006)
"Operation Buccaneer" was the name given to a law enforcement operation against "DrinkOrDie," a highly organised but globally dispersed Internet-based software piracy group. The concerted enforcement action, led by the US Customs Service and Department of Justice, extended to several European countries and Australia. This paper contrasts the legal consequences that flowed, with numerous suspects pleading guilty in the United States, some contested prosecutions in the United Kingdom, and a sole Australian suspect facing extradition to the United States to face charges. Operation Buccaneer illustrates the cross-national reach of both Internet-based intellectual property crime and the law enforcement response, as well as some of the complexities that arise in applying jurisdictional concepts such as the "double criminality" requirement for extradition in this evolving prosecutorial landscape.